2017
DOI: 10.1007/s12640-017-9792-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Utility of Fatty Acid-Binding Protein 4 in Patients with Type 2 Diabetes and Acute Ischemic Stroke

Abstract: The role of fatty acid-binding proteins (FABPs) in atherosclerosis has been investigated. The aim of this study was to verify the hypothesis that higher levels of serum fatty acid-binding protein 4 (FABP4) could be a prognostic factor in Chinese patients with type 2 diabetes (T2DM) and acute ischemic stroke (AIS). From September 2015 to August 2016, consecutive first-ever AIS patients combined with T2DM were included in this study. FABP4, NIH stroke scale (NIHSS), and conventional risk factors were evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…It has been reported that increased circulating FABP4 levels are associated with obesity, insulin resistance, T2DM, cardiovascular disorders, arterial hypertension, cardiac dysfunction, kidney damage, fatty liver disease, and atherosclerosis [10,29,31,32,39,40,41,42]. Increased FABP4 concentrations were found in obese subjects and were positively correlated with waist circumference, blood pressure, and insulin resistance [40].…”
Section: Relationship Between Fabp4 and Diseases Of Civilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that increased circulating FABP4 levels are associated with obesity, insulin resistance, T2DM, cardiovascular disorders, arterial hypertension, cardiac dysfunction, kidney damage, fatty liver disease, and atherosclerosis [10,29,31,32,39,40,41,42]. Increased FABP4 concentrations were found in obese subjects and were positively correlated with waist circumference, blood pressure, and insulin resistance [40].…”
Section: Relationship Between Fabp4 and Diseases Of Civilizationmentioning
confidence: 99%
“…Increased FABP4 production could contribute to macrophage activity, possibly by activation of inflammatory pathways, resulting in inflammation [42]. An alternative hypothesis, more in line with the published evidence, is that the elevated circulating FABP4 reflects the increased cellular production in both adipocytes and macrophages in response to greater lipid availability, with increased Kupffer cell production of FABP4 triggering an increased inflammatory response [42,54].…”
Section: Associations Of Fabp4 With Adipogenesis and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fabp4 IgG signal was much reduced in the SHR-A3(Stim1-B2) congenic line. Fabp4 is a marker of stroke risk [45], a prognostic indicator of stroke outcome [46,47] and is a proangiogenic factor expressed in vascular endothelial cells [48]. The HuProt array poses limitations: first, the arrayed proteins are not rat proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Tso et al [12] showed that serum FABP4 was independently related to stroke (odds ratio [OR] 2.10, 95% confidence interval [CI] 1.50-2.94; P < 0.001), and a high serum level was associated with increased risk of 3-month mortality in ischemic stroke subjects (OR 2.65, 95% CI 1.18-5.96; P = 0.018). High levels of FABP4 were also significantly associated with stroke risk and severity, independent from other risk factors [13], while elevated serum FABP4 levels were associated with poor prognosis in ischemic stroke patients with type 2 diabetes [14].…”
Section: Introductionmentioning
confidence: 89%